Does Economic Growth Contribute to Poverty Reduction? An Empirical Analysis Evidence from Rwanda - Bikorimana, Gerard; Butare, George Wycliffe; Sun, Shengmin (Asian Journal of Economic Modelling, 2018)
This study empirically analyzes whether economic growth contributed to poverty reduction in Rwanda over the period of 1980-2016. The study applied the Autoregressive - Distribution Lag bounds approach to testing for cointegration, as well Toda and Yamamoto (TY) Granger causality was used in testing for the directional causality among the variables in the study. The Autoregressive - Distribution Lag bounds test results confirm the cointegration between Household final consumption expenditure, Arable land growth rate (hectares), Gross capital formation growth rate (% of GDP), Government final consumption expenditure growth rate (% of GDP) and Service value-added growth rate, when the Household final consumption expenditure, Arable land growth rate and Gross capital formation growth rate are used as dependent variable. Additional, the results from Toda and Yamamoto Granger causality confirms a no evidence of causality association linking the poverty reduction to economic growth and vice versa while considering log Household final consumption expenditure and Arable land growth rate as dependent variables. This means that the neutrality hypothesis grips for Rwanda in the period covered by the study. Furthermore, the study finds out a proof of unidirectional causality running from Gross capital formation growth rate to government final consumption expenditure growth rate, as well as unidirectional causality running from Arable land growth rate to Government final consumption expenditure growth rate and Service value-added growth to Government final consumption expenditure growth rate. The study findings suggested that the government should adopt policy’s objective which is focusing on poverty reduction and economic growth.